PSO-based Medical Image Processing for Kienbock Biomechanical Analysis (Journal of Fiber Bioengineering and Informatics, 2015)
Through the lunate bone biomechanical analysis can be used for kienb\u00f6ck medical diagnosis and treatment.\rThe pressure sensitive film can reflect intuitively the stress of lunate bone's each point. This paper obtains\rstress analysis of lunate bone based on PSO (Particle Swarm Optimization) algorithm's image analysis\rand processing of pressure sensitive film. The paper uses the grayscale function to change a target image\rinto the grayscale image, and uses the PSO algorithm for function optimization to segment image with\rthe original image. Then we obtain remaining achieving gray value, and calculate the pressure. Through\rthe analysis of the experimental data, we obtain the maximum value, minimum value and average value\rof the pressure. The analysis of processing results showed that the PSO algorithm could segment the\rimage accurately and the remaining larger pixel gray values concentrated in the three fossa of lunate\rbone. The results verify the accuracy and efficiency of the method.